2019
DOI: 10.1177/1533317519860331
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intuitive Movement Reembodiment on the Quality of Life of Older Adults With Dementia: A Pilot Study

Abstract: Background: The creative use of reminiscent music and natural movements were reported to have positive effects on the well-being of older adults with cognitive impairment. Objectives: To explore the effects of the intuitive movement reembodiment (IMR) program on the quality of life (QoL) of older adults with dementia. Methods: Data collected from 22 participants were analyzed: group 1 (mild dementia), group 2 (moderate dementia), group 3 (advanced dementia). All study groups participated in 10 weekly sessions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In another proposed pathogenic link between NHLH2 and NCDs, CNS heat deregulation appears to have a role in the pathogenesis of neurodegeneration, and the NHLH2 gene is induced following cold and torpor [37]. This gene is linked to motivated exercise and obesity [11,38], which are considered crucial protective and risk factors for late-onset NCDs, respectively [39].…”
Section: Discussionmentioning
confidence: 99%
“…In another proposed pathogenic link between NHLH2 and NCDs, CNS heat deregulation appears to have a role in the pathogenesis of neurodegeneration, and the NHLH2 gene is induced following cold and torpor [37]. This gene is linked to motivated exercise and obesity [11,38], which are considered crucial protective and risk factors for late-onset NCDs, respectively [39].…”
Section: Discussionmentioning
confidence: 99%
“…Three of the reviewed studies were conducted on older adults with some cognitive decline, impairment, or dementia. Two studies ( Treviño and Álvarez-Bermúdez, 2018a ; Fischbacher et al, 2020 ) applied the Dalcroze approach, and one was based on the specially designed intuitive movement re-embodiment (IMR) program in which the music component drew on the Dalcroze approach and the creative movement incorporated ideas from the Laban approach ( Choo et al, 2020 ). The studies reported improvement in positive affectivity, state of flow, quality of life, sense of humor, imagination, motivation for dance, and joyful interaction.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Choo et al (2020) older adults with dementia, who were grouped according to the degree of their dementia, participated in 10 weekly sessions. The data included self-reported ratings of quality of life and qualitative onsite observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this are calls to offer both dance artists (with all their embodied expertise to analyse and interpret movement-based developments) and participants roles beyond the passive and to engage them, and their embodied voice, more in research data collection and protocols (Zeilig et al, 2019 ), also connecting to efforts to move beyond a cognitive emphasis. These perspectives from review papers reflect a move in wider arts for health research towards using arts approaches (Fraser & Sayah, 2011 ), and new approaches (Choo et al, 2019 ) including philosophical analysis techniques in the vein of the rhizomatic approach of Deleuze and Guattari (e.g., Atkinson & Scott, 2015 ) and valuing practitioner reflective practices focused on elements like dialogic, kinaesthetic empathy (Wakeling, 2014 ).…”
Section: Overall Contribution Of Reviewed Research To Answering Research Questionsmentioning
confidence: 99%